Use of desflurane during anesthesia for resection of extra-adrenal pheochromocytoma: a case report - Oda, Yutaka (JA Clin Rep, 2018)
BACKGROUND: Although various agents are used during anesthesia for surgical resection of pheochromocytoma, application of desflurane has rarely been reported. We report the use of desflurane in a case receiving resection of extra-adrenal pheochromocytoma. CASE PRESENTATION: A 51-year-old female was transferred to our hospital for sustained hypertension. A diagnosis of extra-adrenal pheochromocytoma was made based on increased plasma catecholamine levels and radiographic findings. Surgical resection was planned after controlling blood pressure. General anesthesia was induced with propofol and fentanyl, followed by maintenance with desflurane 4.3% and remifentanil 0.2–0.4 μg/kg/min. Blood pressure and heart rate were stable during induction, tracheal intubation, and tumor manipulation. Blood pressure abruptly decreased to 62/40 mmHg after removal of the tumor, which was treated with noradrenaline. The surgery was completed uneventfully and the postoperative course was also uneventful. CONCLUSION: Desflurane was safely used in combination with remifentanil during anesthesia for resection of extra-adrenal pheochromocytoma.